2013
DOI: 10.1016/j.cell.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The Long and Short of MicroRNA

Abstract: MicroRNAs (miRNAs) are versatile regulators of gene expression in higher eukaryotes. In order to silence many different mRNAs in a precise manner, miRNA stability and efficacy is controlled by highly developed regulatory pathways and fine-tuning mechanisms both affecting miRNA processing and altering mature miRNA target specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
455
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 636 publications
(482 citation statements)
references
References 21 publications
3
455
0
11
Order By: Relevance
“…M icroRNAs (miRNAs) are small (17-24 bp), noncoding RNAs that regulate different biological functions by modulating expression and stability of target genes posttranscriptionally (1,2). The role of miRNAs in lung development is currently poorly defined.…”
mentioning
confidence: 99%
“…M icroRNAs (miRNAs) are small (17-24 bp), noncoding RNAs that regulate different biological functions by modulating expression and stability of target genes posttranscriptionally (1,2). The role of miRNAs in lung development is currently poorly defined.…”
mentioning
confidence: 99%
“…24 miRNAs are involved in the regulation of various cell processes including development, apoptosis, proliferation, and differentiation. 1 Further investigations have confirmed that miRNAs can function as tumor suppressors or oncogenes and play essential roles in a wide variety of physiological and pathological processes in various cancers, including glioma.…”
mentioning
confidence: 99%
“…In recent years, many miRNAs targeting complementary sequences in 3 0 UTR have been discovered, and evidence has much increased showing their importance in regulating physiologic and pathologic cellular pathways (36). As camptothecin treatment determines strong modification of transcription of several mRNAs (30,37,38), we questioned if the drug could modulate the miRNAs expression profiles in two human cancer cell lines and, if that was the case, if miRNAs modifications reflect in the HIF-1a protein expression.…”
Section: Discussionmentioning
confidence: 99%